LEXICAL AND CULTURAL DIFFERENCES BETWEEN THE RUSSIAN AND UZBEK LANGUAGES: ISSUES OF INTERCULTURAL COMMUNICATION IN THE TEACHING PROCESS - Nurmatova Faiza Irikovna (Bright Mind Publishing, 2025)
This article explores the lexical and cultural differences between the Russian and Uzbek languages and their impact on the teaching process. Special attention is given to the challenges faced by Uzbek-speaking students in understanding Russian lexical units that carry cultural connotations. The study analyzes how cultural differences influence communication and suggests effective strategies for overcoming intercultural communication barriers in language learning. The findings highlight the importance of integrating cultural components into the language teaching process to improve students' linguistic competence and communicative skills.
Keywords: Intercultural communication, lexical differences, cultural connotations, Russian language teaching, Uzbek-speaking students, linguistic competence, cross-cultural barriers.